Upaya Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Mewarnai Gambar Pada Anak Didik Kelompok A Semester 1 TK Pertiwi Bergolo Kecamatan Ngawen Kabupaten Blora Tahun 2015/2016 - SUSILOWATI, SITI ENDANG; , Drs. Sutan Syahrir Zabda, SH,MH (2015)
This research aims to improve children's fine motor skills by coloring pictures. This research is a classroom action research conducted in two cycles and each cycle outsmart conducted two meetings. The subjects of this study is children Group B TK Pertiwi Bergolo District of Ngawen Blora totaling 15 children as recipients of actions, researcher and teacher colleagues as giving action. The data collected in this study is data about fine motor skills of children and data on teacher learning through activities coloring. Both of these data were collected through observation. Data were analyzed children's fine motor skills with comparative analysis and data on teacher learning through activities coloring pictures were analyzed by interactive analysis. The results of the analysis showed that the average prasiklus fine motor skills a child reaches 59% means that the new children's fine motor skills develop according to expectations. After the first cycle measures the average fine motor skills a child reaches 67%, which means that the child's fine motor skills are still developing according to expectations, but already there is an increase. After the second cycle measures the average fine motor skills children increased 84% means that children develop fine motor skills very baik. Main of this study is that by coloring a picture can improve fine motor skills of children in group B TK Pertiwi Bergolo District of Ngawen Blora